2010
DOI: 10.1002/chem.201000923
|View full text |Cite
|
Sign up to set email alerts
|

Do Trinuclear Triplesalen Complexes Exhibit Cooperative Effects? Synthesis, Characterization, and Enantioselective Catalytic Sulfoxidation by Chiral Trinuclear FeIII Triplesalen Complexes

Abstract: The chiral triplesalen ligand H(6)chand provides three chiral salen ligand compartments in a meta-phenylene arrangement by a phloroglucinol backbone. The two diastereomeric versions H(6)chand(RR) and H(6)chand(rac) have been used to synthesize the enantiomerically pure chiral complex [(FeCl)(3)(chand(RR))] (3(RR)) and the racemic complex [(FeCl)(3)(chand(rac))] (3(rac)). The molecular structure of the free ligand H(6)chand(rac) exhibits at the terminal donor sides the O-protonated phenol-imine tautomer and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 106 publications
(155 reference statements)
3
33
0
Order By: Relevance
“…[2,3] These triplesalen ligands are intended to combine phloroglucinol A, as a ferromagnetic coupler by the spin-polarization mechanism, [4] and the salen-like coordination environment B, which enforces a strong magnetic anisotropy in selected metal ions. [5] Indeed, the characterization of trinuclear Cu II and V IV =O complexes demonstrate the targeted ferromagnetic interactions, [6][7][8] while in Mn III[9] and Fe III [10] complexes, antiferromagnetic interactions prevail. Moreover, the trinuclear complexes of the tert-butyl derivative H 6 -talen tBu 2 exhibit a strong ligand folding, which leads to an overall bowl-shaped molecular structure (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] These triplesalen ligands are intended to combine phloroglucinol A, as a ferromagnetic coupler by the spin-polarization mechanism, [4] and the salen-like coordination environment B, which enforces a strong magnetic anisotropy in selected metal ions. [5] Indeed, the characterization of trinuclear Cu II and V IV =O complexes demonstrate the targeted ferromagnetic interactions, [6][7][8] while in Mn III[9] and Fe III [10] complexes, antiferromagnetic interactions prevail. Moreover, the trinuclear complexes of the tert-butyl derivative H 6 -talen tBu 2 exhibit a strong ligand folding, which leads to an overall bowl-shaped molecular structure (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This calculated model nicely reproduces the experimental structure by the central backbone of H 6 chand rac , although H 6 chand rac exhibits stronger deviations from C 3 symmetry. Nevertheless, the mean O···N distances of 2.50Å compares well to that of H 3 14 Me [53]. The strongest difference is in the C(sp 2 )-N bond (mean value 1.31Å in H 6 chand rac vs. 1.34Å in H 3 14 Me ), which may be related to a cyclohexyl vs. a methyl substituent at the nitrogen atom.…”
Section: 42å In H 3 12)mentioning
confidence: 71%
“…Detailed magnetic studies demonstrated that our trinuclear Cu II 3 [27,36] and V IV 3 [37] triplesalen complexes indeed exhibit ferromagnetic but only weak interactions. However, Fe III [38,39] and Mn III [28-33, 40, 41] ions appeared to be almost uncoupled and even slightly antiferromagnetically coupled through the triplesalen ligand, respectively. Thus, the anticipated spin-polarization through the central phloroglucinol is not efficient.…”
Section: Introductionmentioning
confidence: 99%